Pilot scale evaluation of feasibility of reuse of wine industry wastewater using reverse osmosis system: modeling and optimization. Issue 53 (13th November 2016) - Thirugnanasambandham, K.; Sivakumar, V.; Loganathan, K.; Jayakumar, R.; Shine, K.
Abstract: In this experiment, reverse osmosis (RO) treatment process was investigated under different operating conditions such as pH, flux, transmembrane pressure, and temperature for the wine industry wastewater treatment using response surface methodology. Box–Behnken response surface design with four variables and three levels was used to optimize and study the effect of process parameters. Pareto analysis of variance was done to analyze the result and second-order polynomial model was created to predict the responses. Optimum process parameters were found to be as follows: pH of 10, flux of 70 L/h, transmembrane pressure of 20 bar, and temperature of 30°C. Under these conditions, predicted value of responses was as follows: Color removal of 91%, COD removal of 93%, TDS removal of 97%, permeate flux of 24 L/m 2 h, operating cost of 14 rupees with water recovery of 69%. The properties of RO-treated permeate water were compared with Indian standards and found to be good fit for reuse.